(untitled) - Bundesarbeitsgemeinschaft der Freien Wohlfahrtspflege e.V. (Sozialwirtschaft, 2023)
Sozialwirtschaft informs about trends in social economy and answers questions about organizing and financing social services. The journal presents personalities and corporations of the industry and provides solutions for managing social enterprises. Comments, interviews, and glosses offer significant reference points for managing practice. The journal addresses chairmen and executives of welfare organizations, associations, managers in social services and facilities, advisors in administration and organizations, consultants, scholars,  and students. Website: www.sozialwirtschaft.nomos.de